2020
DOI: 10.21608/adjalexu.2020.86763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microleakage of Silver Nanoparticle-Added Pit and Fissure Sealant in Permanent Teeth (In-Vitro Study)

Abstract: INTRODUCTION: Silver has long been recognized for its antimicrobial effect on a wide spectrum of microorganisms. Consequently, silver nanoparticles became among the most common therapeutic nanoparticles under research in the field of caries prevention. Pit-and-fissure sealants are among the major components in the field of caries prevention which could have an additional antibacterial benefit through silver nanoparticles addition. OBJECTIVES:The aim of the study was to evaluate, in-vitro, the marginal seal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Our finding that fissure pre-treatment with NSF didn't affect micro-leakage scores of the FS was supported by Morales et al, (34) and Khairy et al (35) who concluded that that there was no significant difference in the marginal seal or micro-leakage between the silver nanoparticle-containing sealant and the conventional sealant when applied in primary molars or permanent premolars respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Our finding that fissure pre-treatment with NSF didn't affect micro-leakage scores of the FS was supported by Morales et al, (34) and Khairy et al (35) who concluded that that there was no significant difference in the marginal seal or micro-leakage between the silver nanoparticle-containing sealant and the conventional sealant when applied in primary molars or permanent premolars respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Duration of exposure at each temperature was 20 seconds. (26) After thermocycling, all surfaces of (16) molars were coated with two layers of nail varnish except for 1.5mm from the sealant margins. Then immersed in a 1% solution of methylene blue for 24 hrs, rinsed with distilled water, dried, and sectioned longitudinally in a bucco-lingual direction using a water-cooled diamond disk.…”
Section: Measurement Of Microleakagementioning
confidence: 99%
“…Another possible limitation would be that extracted teeth do not have the pulp pressure and intratubular fl uid pressure as in natural teeth. This could have an impact on tooth moisture level, aff ecting microleakage at tooth restoration interface 34 . While in another study, the addition of silver NPs in sealants reduced tooth demineralization signifi cantly.…”
Section: Silver (Ag) Npsmentioning
confidence: 99%